ANALISIS POLA ASUH KELUARGA NELAYAN DALAM MENDIDIK ANAK DI DUSUN BATU RAWAN SEMANGIT - Halimah, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to determine the pattern of family foster fishermen in educating children in Dusun Batu Rawan Semangit Selimbau Sub-district Kapuas Hulu District in the form of permissive, authoritarian and democratic parenting. The method used is qualitative method with descriptive analysis. The data collection tool is using observation guides, interview guides, and documentation tools. The results of this study indicate that the permissive parenting pattern applied by the fishermen families in educating children is indifferent to children, giving full freedom to the activities of children, no guidance or direction, and control and attention to children is very less then the pattern of authoritarian parenting Such as being pushy, hard, making rules to be obeyed by children, and quickly emotional and angry if children do things that are not in accordance with the desired by their parents, while the democratic parenting is to give freedom to children, and there is good supervision From parents to their children. Keywords: Patterns of Custody, Family of Fishermen, Educating Children